Implementasi Algoritma Genetika pada Perancangan Aplikasi Penjadwalan Instalasi Antivirus Berbasis Website menggunakan Metode Waterfall - Nugraha, Yoga Septian; Darusalam, Ucuk; Iskandar, Agus (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Scheduling is the activity of planning in conducting activity at a certain time. The main objective of the scheduling is to improve the effectiveness and the efficiency of the use of resources so that progress that has been determined previously achieved well. A genetic algorithm is one of the most often algorithms used in optimization scheduling. This algorithm works based on a natural process carried out using heuristic methods. One of the scheduling problems at company x in the step to increase security through system security updates with this antivirus installation program involves all employees as users of each division and handled by the IT team as the pic that handles the program. Scheduling is still compiled manually so that raises some of the problems starting from the preparation process to the division of the schedules to require a long time, it usually tends to clashes between the hour and the day when the PIC handles the user due to not automatic scheduling. Therefore, designing an application system by using web-based programming is conducted waterfall method to ease in the process of the preparation and distribution of a schedule which is more systematic with the implementation of the method of the genetic algorithm so that the scheduling that there will be more optimal.